JAK2V617F: Is It Sufficient as a Single Player in Splanchnic Venous Thrombosis? - Dhiman, Pratibha (Case Rep Hematol, 2015)
Splanchnic venous thrombosis (SVT) includes thrombosis of the hepatic, portal, and mesenteric venous system. Myeloproliferative neoplasms (MPNs) are important factors of SVT in adults. Addition of JAK2V617F mutation in WHO criteria for diagnosis of MPNs has made this test a useful tool for diagnosis. JAK2 is an intracytoplasmic tyrosine kinase that plays a critical role in signal transduction from multiple hematopoietic factor receptors. The mutation is found frequently in patients with SVT; many such patients have no other manifestations of an MPN. Although the correlation of JAK2V617F mutation with thrombotic risk in MPNs has been shown in many studies, the impact of presence of additional thrombophilic factors in these cases is yet not known. As the management of MPNs remains highly dependent on the patient's thrombotic risk, it is important to assess the thrombotic risk factors in detail. Here, we report two cases of JAK2V617F positive MPN who also had other thrombophilic conditions and presented with recurrent thrombosis.